Analysing mobile learning designs: A framework for transforming learning post-COVID - Cochrane T; Narayan V; Aiello S; Alizadeh M; Birt J; Bone E; Cowie N; Cowling M; Deneen C; Goldacre P; Sinfield D; Stretton T; et al. (ASCILITE, 2022)
Mobile learning is well established in literature and practice, but under-evolved from a rigorous learning design perspective. Activity theory presents a sophisticated way of mapping and understanding learning design, but for mobile learning this does not always translate into change in practice. The reported research addresses this by coupling a mobile learning specific approach to activity theory with a practice-based framework: the design for transformative mobile learning framework mapped to the pedagogy-andragogy-heutagogy continuum matrix (the DTML-PAH Matrix). Seven case studies are analysed using this approach and presented narratively along with framework informed analysis. Findings include that the DTML-PAH Matrix can be used to provide clearer implications and guidance for mobile learning practice, and that the DTML-PAH Matrix can also be guided by the practice over time. Implications for further research and practice are discussed. Implications for practice or policy: Provide technological and pedagogical scaffolds to students. Learning designs should focus upon enabling elements of learner agency and creativity. To develop learning solutions to real world problems utilise a design-based research approach. Create authentic collaborative learning activities and tasks. Integrate mobile learning affordances in the design of the course and curriculum.
Copyright (c) 2022 The Author/s